Left ventricular diastolic function in mitral stenosis - Venkateshvaran, Ashwin; Govind, Satish C. (Echocardiography (Mount Kisco, N.Y.), 2020)
The assessment of left ventricular (LV) function in the setting of mitral stenosis (MS) has been critically examined for decades. Accurate assessment of aberrations in diastolic function is important as these subjects often present with signs and symptoms of heart failure and pulmonary congestion that cannot be solely explained by the severity of mechanical obstruction. Echocardiographic evaluation of diastolic dysfunction includes an evaluation of reduced LV compliance, diminished restoring forces, and enhanced stiffness, which are challenging in the setting of MS owing to altered hemodynamic loading. Conventional echocardiographic and Doppler measures offer limited information. Novel assessments employing speckle tracking echocardiography are relatively less studied. A more comprehensive assessment including clinical evaluation, identification of concomitant disorders, and comorbidities is particularly warranted in older subjects with degenerative MS to suspect diastolic dysfunction and arrive at optimal medical therapy or intervention. This review provides an overview of etiological, pathophysiological, echocardiographic, and invasive assessment of diastolic dysfunction in the setting of MS, with specific focus on strengths and limitations of available echocardiographic and Doppler techniques.